ESTETIKA DAN NILAI PENDIDIKAN KARAKTER PANJI SEMIRANG DALAM HIKAYAT KARYA SALEH SASTRAWINATA - Nur Adriatika Anggraini (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2018)
This study aims to describe the beauty of the ontological, immanent, and psychological aspects, as well as the character education values ??contained in the Panji Semirang story by Saleh Sastrawinata. The type of research used in this study is qualitative descriptive. The source of the data in this study is a literary work, namely the Panji saga of semirang sastrawinata. The data in this study are text, words, sentences, or paragraphs that contain ontological, immanent, psychological aspects, as well as the value of character education. This research was obtained using reading, note taking and literature study methods. The results of this study show the beauty that is divided into three parts in ontological aspects, namely: strength, wealth, and greatness of God. The results of the research in the immanent aspect are three parts, namely: something unusual, something that is not singular, and orderly, orderly and harmonious sound. The results of the research in the psychological aspect consist of two parts, namely: positive psychiatric and negative psychiatric, as well as the value of character education. Keywords: Aesthetics, Hikayat, Panji Semirang, Value of Character Education.